ICXT characterization in WC-MCFs and its impact on the performance of OOK-DD systems - Cartaxo, A. V. T.; Alves, T. M. F.; Rebola, J. L. (2022 13th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP), 2022)
An overview of some of our results on the intercore crosstalk (ICXT) induced in weakly-coupled multicore fiber (WCMCF) systems is presented. The random evolution of the ICXT over time observed experimentally in WC-MCFs is characterized and the correlation between the ICXT field components induced by multiple interfering cores is investigated. The impact of the ICXT on the outage probability of on-off keying direct-detection WC-MCF systems, with |skew×bitrate|≪1 and | skewxbit rate |≫1, is assessed as well. It is shown that the ICXT power induced by multiple interfering cores is adequately modelled by a ?2 distribution with four degrees of freedom. This means that the ICXT Gaussian field components are uncorrelated or weakly correlated. The measurements of the system performance show that, for the same outage probability, systems with | skewxbit rate |≫1 present an additional ICXT tolerance of about 3 dB compared with systems with |skew×bitrate|≪1.